Review of 52 cases with Hailey–Hailey disease identified 25 novel mutations in Chinese Han population. Issue 11 (21st August 2019) - Wang, Zhe; Li, Lulu; Sun, Lele; Mi, Zihao; Fu, Fanghui; Yu, Gongqi; Fu, Xian; Liu, Hong; Zhang, Furen
Abstract: Hailey–Hailey disease (HHD) is a rare autosomal dominant inherited keratosis caused by mutations in ATP2C1 . The aim of our study was to identify and analyze the features of the mutations in HHD. We examined 52 Chinese Han cases which were diagnosed as HHD based on their clinical and histological findings. Genomic DNA polymerase chain reaction and direct sequencing of ATP2C1 were performed from peripheral blood samples of the patients and 100 unrelated healthy controls. Twenty‐five novel mutations and 14 recurrent mutations were identified, including 11 (28.2%) missense mutations, nine (23.1%) frame‐shift deletion mutations, eight (20.5%) nonsense mutations, seven (17.9%) splicing mutations and four (10.3%) frame‐shift insertion mutations. Together with ours, all 209 mutations showed a uniform distribution without hotspots or clusters. In addition, there is no specific genotype–phenotype correlation in HHD. Our findings update the spectrum of mutations in ATP2C1 .